If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2X) + -13 = X + 12 Reorder the terms: -13 + (2X) = X + 12 Reorder the terms: -13 + (2X) = 12 + X Solving -13 + (2X) = 12 + X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. -13 + (2X) + -1X = 12 + X + -1X Combine like terms: (2X) + -1X = 1X -13 + 1X = 12 + X + -1X Combine like terms: X + -1X = 0 -13 + 1X = 12 + 0 -13 + 1X = 12 Add '13' to each side of the equation. -13 + 13 + 1X = 12 + 13 Combine like terms: -13 + 13 = 0 0 + 1X = 12 + 13 1X = 12 + 13 Combine like terms: 12 + 13 = 25 1X = 25 Divide each side by '1'. X = 25 Simplifying X = 25
| 7n+3(4n+8)=5 | | 3t-29=32+4t | | 4x+11y=213 | | X+12=(2*x)-13 | | 4.3x=4.3x | | 4y-32=12x | | (5x-1)+(2x+3)= | | 3y-10-15y=-6y+14 | | 4+8r=-4+7r | | 5.5x+7-1.5x=3.2-3 | | 3w+9=-15 | | X-3-6=-9 | | 5+[3]n=29 | | (11y+2)=130.42 | | 0.25+4=0.4(n+4) | | 2(-8+k)=18 | | f(-x)=4x^2-2x+8 | | 9(x^2+4x+4)=0 | | 3=3+5k | | v(j+y)=61y+82 | | -3=4-7r | | 6a^2-3.6a=0 | | 8x+6x=42 | | C^2+4x+4=0 | | 24(a-4)+13-3+55-9+44= | | -3(3r+6)+4(r+5)=-28 | | f(x)=-2x^2-10x+12 | | -4(x-8)-2(x+5)=70 | | 4p-12=-47+9p | | X-13=(.5*X)+12 | | 100-41.75=2x | | 9.4x=47 |